Phenol-Soluble Modulins Modulate Persister Cell Formation in Staphylococcus aureus - Baldry, Mara; Bojer, Martin S.; Najarzadeh, Zahra; Vestergaard, Martin; Meyer, Rikke Louise; Otzen, Daniel Erik; Ingmer, Hanne (Frontiers in Microbiology, 2020)
SStaphylococcus aureus is a human pathogen that can cause chronic and recurrent infections recalcitrant to antibiotic chemotherapy. This trait is partly attributed to its ability to form persister cells, which are subpopulations of cells tolerant to lethal concentrations of antibiotics. Recently, we showed that the phenol-soluble modulins (PSMs) expressed by S. aureus reduce persister cell formation. PSMs are a versatile group of toxins that in addition to toxicity form amyloid-like fibrils thought to support biofilm structures. Here we examined individual or combined synthetic PSM peptides and their equivalent amyloid-like fibrils on ciprofloxacin-selected S. aureus persister cells. We found that PSM2 and the mixture of all four alpha peptides consistently were able to reduce persister frequency in all growth phases, and this activity was specifically linked to the presence of the soluble peptide as no effect was seen with fibrillated peptides. Persister reduction was particularly striking in a mutant that, due to mutations in the Krebs cycle, has enhanced ability to form persisters with PSM4 and the combination of peptides being most effective. In biofilms only the combination of peptides displayed persister reducing activity. Collectively we report the individual contributions of PSM peptides to persister cell reduction and that the combination of peptides generally was most effective. Strikingly the fibrillated peptides lost activity and thus, if formed in bacterial cultures, they will be inactive against persister cells. Futher studies will be needed to address the biological role of phenol-soluble modulins in reducing persister cells.